The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ekir.2019.05.831
|View full text |Cite
|
Sign up to set email alerts
|

Mon-044 Prediction of Outcomes of Rapidly Progressive Glomerulonephritis

Abstract: disease stage 1~2. For hyperuricemic patients, the response rate to therapy and renal survival rate were significantly higher in patients that received RAS blockade in combination with immunosuppression. Conclusions: Hyperuricemic IgAN patients presented more severe clinical characteristics. Tubulointerstitial injury could be a pathological feature closely related to hyperuricemia in IgAN. Immunosuppression could reduce proteinuria and improve renal outcome in IgAN patients with hyperuricemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, infections, heart failure, and diabetes were all present in 67.2%, 29.09%, and 29.09% of the patients, respectively, according to Wangnoo et al [5]. According to Sandhu's study, infections and neutropenia (55 and 40%, respectively) were the two most frequent secondary outcomes [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, infections, heart failure, and diabetes were all present in 67.2%, 29.09%, and 29.09% of the patients, respectively, according to Wangnoo et al [5]. According to Sandhu's study, infections and neutropenia (55 and 40%, respectively) were the two most frequent secondary outcomes [32].…”
Section: Discussionmentioning
confidence: 99%
“…10 patients (25%) died during the study's duration. Infections accounted for 50% of causes of death, followed by cardiovascular disease (30%), stroke (10%), and unknown in 10% of cases [32]. Alexander et al 's research revealed that serum creatinine at presentation (P < 0.001), oliguria (P < 0.001), percent of crescents (P < 0.001), mesangial proliferation (P = 0.01), and IFTA (P < 0.001) were all shown to be ESRD predictors by univariate logistic regression.…”
Section: Discussionmentioning
confidence: 99%